Analisis Transmisi Kebijakan Moneter Melalui Saluran Harga Aset di Sektor Finansial - Yolanda Argi Utami; Thomas Andrian; Ukhti Ciptawaty (Goodwood Publishing, 2022)
The purpose of this study is to examine the variables of the policy transition mechanism through the financial sector when changes in each variable and the contribution of the SBK, rPUAB, IHSGI, KONS, and INF variables to the final target of monetary policy and inflation. The data used in this study is secondary data sourced from the official website of Bank Indonesia (BI) and the Central Statistics Agency (BPS). This study uses time series data from the period 2010Q1 to 2021Q4. The analytical method used is the Vector Error Correction Model (VECM) with the analysis of Impulse Responses (IR) and Variance Decomposition (VD). The results of this study indicate that based on the test results of the impulse response variables SBK, rPUAB, IHSG, and KONS respond quickly to changes in each variable in the initial period after the shock occurs. The results of the analysis of variance decomposition showed that apart from the INF variable itself, each variable had a different contribution to the INF level with the order of the greatest influence being IHSG, KONS, rPUAB, OG, SBK and rDEPO.